Precompetitive anxiety effect on concentration and performance on elite rhythmic gymnasts - Nassib, S. H.; Mkaouer, B.; Nassib, S.; Riahi, S. H.; Arfa, Y. (Science of Gymnastics Journal, 2014)
The multidimensional conceptualization of competitive anxiety incorporating cognitive and somatic components has provided a clearer understanding of how athletes respond to competitive stressors (see Jones, 1995; Woodman and Hardy, 2001 for a review). Thus, in competition, some athletes anxiety tend to dissipate their attention resources and to identify threats to stimuli that disrupt the running of the race. In addition, each athlete has suffered a break in concentration followed by a decline in performance and loss of confidence. So, the purpose of the present study was to examine the relationship between competitive anxiety, concentration and performance of gymnastics athletes at different time of assessment. Data for this study were collected from 6 competitive female rhythmic gymnasts in the highest national team (age 14.8 ± 1.3 years, weight 77.5 ± 7.1 kg, height 180.8 ± 5.6 cm). Descriptive statistics revealed that the scores of cognitive anxiety increased from 15.83 ± 1.835 in the training condition to 19.67 ± 2.160 for the competition condition. Regarding somatic anxiety has increased from 15.50 ± 1.517 to 19.67 ±, 816 during the competition condition. In contrast, the average self-confidence has diminished from 21.00 ± 1.414 to 17.50 ± 1.871 during the competition. Accordingly, the importance of collecting information on how anxiety changes during the course of a competition appears fundamental to improving the predictive value of theories that seek to explain how such anxiety may influence athletic performance.